Manajemen Strategis Pemasaran Untuk Meningkatkan Kunjungan Pasien Pada Pelayanan Rawat Jalan Di Klinik Pratama Melania Burderan Bogor - Fahik, Agustinus; Sumihar Sitorus, Rotua; Melda Bangun, Sri (Jurnal Riset Hesti Medan, 2023)
Marketing management is part of the progress of a product or a business. The Primary Clinic of Melania Bruderan Bogor was created a marketing organizational structure as an effort to carry out promotion and marketing with the hope of increasing the count of patient visits for outpatient services, increasing clinic revenue and making the good image of the clinic that has been formed to be better known for the public. Marketing management concerns of mission statements, goals or objectives and strategic focus, including in this case of segmentation, targeting and positioning. Marketing management in outpatient services is based on a situation analysis which results in a strategic position for the Melania Bruderan Bogor Primary Clinic to deal with existing competitive conditions through the use of the TOWS matrix and the IE matrix. Strategic priority determination is carried out using the QSPM matrix and the CDMG method. After obtaining the appropriate strategic priorities, based on the results of the total TAS assessment from the QSPM matrix, then determine the target description. The description of the objectives is useful for achieving the objectives of the existing strategy. This study suggests the management of the Melania Bruderan Primary Clinic in Bogor to be able to apply marketing strategy management to increase the number of visits to outpatient services because they are considered appropriate to clinical conditions. The management only needs to make planning and marketing activities in accordance with the description of the goals that are made as input from the chosen strategy so that the targets desired by the clinic are achieved.